Adolescent idiopathic scoliosis (AIS): a multifactorial cascade concept for pathogenesis and embryonic origin. Issue 1 (December 2016) - Burwell, R.; Clark, Emma; Dangerfield, Peter; Moulton, Alan
Abstract This paper formulates a novel multifactorial Cascade Concept for the pathogenesis of adolescent idiopathic scoliosis (AIS). This Concept stems from the longitudinal findings of Clark et al. (J Bone Miner Res 29(8):1729-36, 2014) who identified leptin body composition factors at 10 years of age associated with a scoliosis deformity found at 15 years. We interpret these findings in the light of some concepts for AIS pathogenesis. In particular, we speculate that the leptin body composition effect is linked to central nervous system development and the initiation of the asynchronous neuro-osseous growth mechanism that involves the creation of a neuraxis tether of relative anterior vertebral overgrowth. The latter mechanism in combination with age and gender-related anatomical variants of vertebral backward tilt (dorsal shear concept), human upright posture, adolescent growth factors, Hueter-Volkmann effect in vertebrae and vertebral bone mass abnormalities, lead to AIS, possibly both initiation and progression of scoliosis curvatures. Being multifactorial, while the Cascade Concept cannot be tested for all its components, some components should be testable by the method of numerical simulation. Clark et al. (J Bone Miner Res 29(8):1729-36, 2014) also suggested the origin of scoliosis was in the embryonic stages of life from cell types, including adipocytes and osteoblasts, derived from the same progenitor cells, and myoblasts from mesodermal somites. The involvement of cell types from different developmental origins suggests a process acting in embryonic life at a similar time, probably environmental, as previously proposed from anthropometric studies. As a Complex disease, AIS will involve genetic, environmental and life style factors operating in development and growth; this possibility needs evaluating in epidemiological studies.